Programmed cell death in seeds of angiosperms - Lopez Fernandez, Maria Paula (2015)
During the diversification of angiosperms, seeds have evolved structural, chemical, molecular and physiologically developing changes that specially affect the nucellus and endosperm. All through seed evolution, programmed cell death (PCD) has played a fundamental role. However, examples of PCD during seed development are limited. The present review examines PCD in integuments, nucellus, suspensor and endosperm in those representative examples of seeds studied to date.